Patient Willingness to Dispose of Leftover Opioids After Surgery - Phoebe Draper, MD; Josh Bleicher, MD, MS; Jaqueline K. Kobayashi, BS; Elizabeth L. Stauder, BS; Gregory J. Stoddard, MBA, MPH; Jordan E. Johnson, CHES, MPH; Jessica N. Cohan, MD, MAS, FACS; Kimberly A. Kaphingst, ScD; Alex H. S. Harris, PhD, MS; Lyen C. Huang, MD, MPH, FACS, FASCRS (Annals of Surgery Open, 2022)
Objectives:. We examined how convenience and financial incentives influence patient willingness to dispose of leftover prescription opioids after surgery. We also identified additional barriers and facilitators to disposal. Background:. In the United States, up to 70% of surgical patients are prescribed opioids and up to 92% will have leftover tablets. Most do not dispose of leftover opioids, increasing the risk for opioid-related harm. Current interventions promoting opioid disposal have shown mixed success. Methods:. We conducted a mixed methods study using a standard gamble survey and semi-structured interviews. Participants estimated willingness to dispose in 16 scenarios with varying convenience (time requirements of <5, 15, 30, and 60 minutes) and financial incentives ($0, $5, $25, $50). We estimated the likelihood of disposal using a multivariable mixed effects modified Poisson regression model. Semi-structured interviews explored how convenience, financial incentives, and other barriers and facilitators influenced decisions to dispose. Results:. Fifty-five participants were surveyed and 42 were interviewed. Most were willing to dispose when the time required was <15 minutes. Few were willing to dispose if the process required 60 minutes, although a $50 financial incentive increased rates from 9% to 36%. Anxiety about future pain, opioid scarcity, recreational use, family safety, moral beliefs, addiction, theft, and environmental harm also influenced decision-making. Conclusions:. Interventions promoting opioid disposal should focus on convenience, but the selective use of financial incentives can be effective. Tailoring interventions to individual barriers and facilitators could also increase disposal rates.